Analisis Manajemen Keuangan dalam (Menilai Kinerja Keuangan) Kelompok Swakelola Masyarakat Program (Kotaku) Kampung Fraboh Tahun Anggaran 2021 - Hulda Serekaya; James Kastanya; Agnes Eyne Banea (Journal on Education, 2023)
This study aims to analyze financial management in assessing the financial performance of the community self-managed group of the Kotaku Kampung Fraboh program for the 2021 fiscal year before and 2 years after the 2020 BPM funds in the Kotaku program of financial assistance provided from the center. The financial performance of the Kotaku Program community self-managed group is measured using financial ratios, namely: Current ratio, Quick Ratio, Cash Ratio, Debt to Asset Ratio, Debt to equity ratio and. Debt to equity The community self-management group took one ksm for the sample in this study as many as 1 community self-management group selected by purposive sampling technique with the type of data collection carried out by collecting secondary data and analyzing financial management in assessing the financial performance of the community self-management group Kotaku program Kampung Fraboh for the 2021 fiscal year contained in the financial statements. These samples were analyzed using the Ratio method. The results of this study indicate that the Debt to Equity Ratio and return on equity show a significant increase in financial performance after the Kotaku Program compares with BPM funds for the 2020 fiscal year. Meanwhile, the return on total assets, Total asset turnover and Current Ratio show no difference in recording community self-management group Kotaku program.